150 Lipid Abnormality, Current Diabetes and Age Affect Erectile Hardness ∼ An Analysis of Data from Complete Medical Checkups Performed at a Single Hospital in Japan. (1st May 2022) - Ishikawa, K.; Sasaki, H.; Ogushi, Y.; Niikura, A.; Ota, T.; Ichimura, Y.; Hashimoto, Y.; Kurokawa, I.; Sugishita, H.; Tanifuji, S.; Yamagishi, M.; Shimoyama, H.; et al.
ABSTRACT: Objectives: The Erection Hardness Score (EHS) can assess erectile hardness with a single question and is readily used in routine clinical practice. We investigated the correlation between EHS and both erectile function and metabolic risk, lifestyle, and other factors. Methods: This study included 548 men who underwent a complete standard medical checkup at our hospital between July 1, 2016, and August 31, 2018, and answered the question about erectile hardness. The following variables were evaluated: age, erectile hardness on the EHS, erectile function on the Sexual Health Inventory for Men (SHIM), current medical history (diabetes, hypertension, dyslipidemia, heart disease, stroke), metabolic risk factors (abdominal circumference, hyperglycemia, high blood pressure, lipid abnormality), and lifestyle factors. First, to examine the correlation between erectile hardness and erectile function, the mean SHIM score by EHS grade was determined for each age group. Then, an analyses was performed to examine the association between erectile hardness and age, current medical history, metabolic risk factors, and lifestyle factors. Results: In each age group, a lower EHS grade was associated with a lower mean SHIM score. Lipid abnormality, diabetes, and age were independent risk factors for decreased erectile hardness. Conclusion: The EHS as a measure of erectile hardness was correlated with erectile functional as assessed using the SHIM, and current diabetes and lipid abnormality were independent risk factors for decreased erectile hardness. However, neither dyslipidemia nor lipid abnormality is listed as a risk factor in the ED guidelines. Traditionally, lipid abnormality was assessed based mainly on the presence or absence of current hyper-lipidemia and serum total cholesterol level. Today, the diagnostic criteria for metabolic syndrome proposed by the World Health Organization, International Diabetes Federation, and Japanese Society of Internal Medicine also recommend the use of serum triglyceride and HDL cholesterol levels, instead of total cholesterol level, for evaluating lipid abnormality. I think the assessment of lipid abnormality should be used triglyceride and HDL cholesterol levels, instead of total cholesterol level. Disclosure: Work supported by industry: no.